2021
DOI: 10.7494/geol.2021.47.1.33
|View full text |Cite
|
Sign up to set email alerts
|

A regurgitalite of the Middle Triassic (Muschelkalk) from Upper Silesia (Poland)

Abstract: A bromalite from the Middle Triassic (Muschelkalk) of southern Poland, Sadowa Góra Quarry, is herein described and interpreted as a regurgitalite. The fossils occurring within the regurgitalite are angular and have sharp edges. They are represented by common fragments of thin-shelled bivalves as well as rare crinoid and gastropod remains. The composition of the collected inclusion is different from that of the host rock. There are many candidates that could have produced the regurgitalite, including durophagou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The conducted research confirmed the purposefulness of the revitalization of post‐mining objects in the city of Jaworzno, most often recommending combining many functions, while the protection and access to geological objects revealed during operation and the use of post‐mining objects for recreation and sports has been recommended as the leading direction of transformation (a total of 95.4%). It was found that customer opinions in the form of direct interviews and the results of scientific research carried out in the Sadowa Góra quarry in Jaworzno in the field of geology (Niedźwiedzki et al, 2021; Surmik et al, 2014, 2020) may be an effective object management tool. This is evidenced by the high ratings given by the respondents and the steady increase in the number of visitors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The conducted research confirmed the purposefulness of the revitalization of post‐mining objects in the city of Jaworzno, most often recommending combining many functions, while the protection and access to geological objects revealed during operation and the use of post‐mining objects for recreation and sports has been recommended as the leading direction of transformation (a total of 95.4%). It was found that customer opinions in the form of direct interviews and the results of scientific research carried out in the Sadowa Góra quarry in Jaworzno in the field of geology (Niedźwiedzki et al, 2021; Surmik et al, 2014, 2020) may be an effective object management tool. This is evidenced by the high ratings given by the respondents and the steady increase in the number of visitors.…”
Section: Resultsmentioning
confidence: 99%
“…Sadowa Góra (Figure 1) quarry is an rea of a lower rank but can be seen as a good example of a space effectively used for public benefit, combining all the most important features of non‐reclaimed post‐mining sites, landscape and educational: fossil remains of vertebrates, echinoderms, brachiopods, etc. (Niedźwiedzki et al, 2021; Surmik et al, 2014, 2020). The quarry is a highly valued tourist attraction because of its scenic qualities, as well as its technical infrastructure elements representing historical value and development elements defining the quality of conditions for use of the facility by end‐users.…”
Section: Research Areamentioning
confidence: 99%
See 2 more Smart Citations
“…2021; Niedźwiedzki et al . 2021). However, until recently, the absence of a univocal terminology (e.g.…”
mentioning
confidence: 99%